2019
DOI: 10.3389/fpsyg.2019.00465
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Competence Level: The Contribution of Non-symbolic and Spatial Magnitude Comparison Skills

Abstract: Magnitude comparison skills have been related to mathematics competence, although results in this area vary. The current study aimed to describe the performance of 75 children (aged 4–5 years) in two comparison tasks; and examine the strength of the relationship between each of the two tasks and mathematics competence level (MCL). Participants were assessed with the Early Numeracy Test which provides a global MCL score. Magnitude comparison skills were assessed with two tasks: a non-symbolic number comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…On the other hand, as shown in all cases, the percentage of variability in academic competencies that is explained by the different specific motor skills varied from R 2 adj = 0.196 to R 2 adj = 0.274. In the humanities and social sciences, these R 2 adj values lie within an acceptable range, with these values being quite typical (and even other lower ones) in many education studies, some of which also focus on the explanation of academic performance (Oliveira et al, 2017;Pires et al, 2017;Cueli et al, 2019;Morales-Rodríguez et al, 2019;Schorr, 2019;Xiao et al, 2019;Tinajero et al, 2020). Social phenomena are complex and multidimensional, so it is not expected that all relevant variables indicating the subject's behavior will be included.…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, as shown in all cases, the percentage of variability in academic competencies that is explained by the different specific motor skills varied from R 2 adj = 0.196 to R 2 adj = 0.274. In the humanities and social sciences, these R 2 adj values lie within an acceptable range, with these values being quite typical (and even other lower ones) in many education studies, some of which also focus on the explanation of academic performance (Oliveira et al, 2017;Pires et al, 2017;Cueli et al, 2019;Morales-Rodríguez et al, 2019;Schorr, 2019;Xiao et al, 2019;Tinajero et al, 2020). Social phenomena are complex and multidimensional, so it is not expected that all relevant variables indicating the subject's behavior will be included.…”
Section: Discussionmentioning
confidence: 86%
“…Past studies of meta-analyses also stated the significant correlations between numerical skills and mathematics (Schneider et al, 2018) and numerous studies had shown a predictive association between mathematical performance and number comparison skills (e.g., Feigenson et al, 2013;Starr et al, 2017). Aside from that, the magnitude comparison task can evaluate the mental representation and processing of numerical magnitudes (De Smedt et al, 2009;Cueli et al, 2019), which can predict mathematical competence (Schneider et al, 2018). All the five constructs in this study are related to one another and essential as a basic mathematics foundation before the children start primary school.…”
Section: Figure 1: Level Of Numeracy Skills Based On the Constructmentioning
confidence: 99%
“…Sin embargo, los antecedentes de las relaciones bivariadas positivas y significativas entre cada una de ellas y las puntuaciones alcanzadas por el alumnado en la competencia matemática temprana, permiten conjeturar que su efecto pudo no ser capturado por el bajo tamaño de la muestra, más aún cuando los intervalos de confianza de los valores de beta estandarizados son amplios. Adicionalmente, estudios confirman que estos dos componentes de la función ejecutiva no solo se asocian a un desempeño incremental de la memoria de trabajo, al actuar como un filtro de información relevante (Cueli et al, 2020), sino que además, se ha constatado su relación significativa con diversos tipos de tareas de matemática temprana como el conteo, la subitización, la correspondencia y los conjuntos numéricos, por nombrar algunas (Cheung & Chan, 2022;Purpura et al, 2017).…”
Section: Discusión Y Conclusionesunclassified